Multistep adhesion of plasmodium sporozoites - Hegge, Stephan; Münter, Sylvia; Steinbüchel, Marion; Heiß, Kirsten; Engel, Ulrike; Frischknecht, Friedrich (The FASEB journal, 2010)
Adhesion of eukaryotic cells is a complex process during which interactions between extracellular ligands and cellular receptors on the plasma membrane modulate the organization of the cytoskeleton. Pathogens particularly rely often on adhesion to tissues or host cells in order to establish an infection. Here, we examined the adhesion of Plasmodium sporozoites, the motile form of the malaria parasite transmitted by the mosquito, to flat surfaces. Experiments using total internal reflection fluorescence microscopy and analysis of sporozoites under flow revealed a stepwise and developmentally regulated adhesion process. The sporozoite-specific transmembrane proteins TRAP and S6 were found to be important for initial adhesion. The structurally related protein TLP appears to play a specific role in adhesion under static conditions, as tlp(−) sporozoites move 4 times less efficiently than wild-type sporozoites. This likely reflects the decreased intradermal sporozoite movement of sporozoites lacking TLP. Further, these three sporozoite surface proteins also act in concert with actin filaments to organize efficient adhesion of the sporozoite prior to initiating motility and host cell invasion.